Al-Ṭuqūs wa ‘alāqatuhā bi huwīyat muslimī Ulu Kapuas, Kalimantan al-Gharbīyah - Ibrahim, Ibrahim (Studia Islamika, 2018)
This article discusses a tradition of Muslim-Malay communities in the context of ritual and cultural identity. This study focuses on the Pangil tradition which are carried out by Muslim-Malay communities in Ulu Kapuas, West Kalimantan. This tradition is carried out by inviting the surrounding communities to commemorate the various events that they have been experienced, either joyful or sorrowful experiences. This article reviews the Pangil tradition by using anthropological perspectives to see patterns of cultural communication and their relationship with identities that represent the Muslim-Malay community. This tradition shows that the balance of life - both in the social and divine dimensions - is highly upheld by the Muslim-Malay community in the Ulu Kapuas. This can be seen in the ritual context which is filled with providing meals, recitating the Al-Quran, and praying for their ancestors. In the context of cultural communication, the Pangil ceremony teaches four things; the value of gratitude to God (nyelamat), sharing joy and sorrow (nyelamatand beruwah), social equality (banquet procession); and togetherness and helping each other (organizing tradition).